2020
DOI: 10.3390/foods9030359
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity and Mechanism of Action of the Amaranthus tricolor Crude Extract against Staphylococcus aureus and Potential Application in Cooked Meat

Abstract: Amaranthus tricolor has been reported to contain some antimicrobial compounds, such as alkaloids, polyphenols, and terpenoids. However, its effect on Staphylococcus aureus has been less well researched. Therefore, this study was designed to evaluate the antimicrobial activity and possible mechanism of action of the Amaranthus tricolor crude extract (ATCE) against S. aureus and potential application in cooked meat. The antimicrobial activity against S. aureus was assessed by disk diffusion, minimum inhibitory c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 32 publications
5
33
0
7
Order By: Relevance
“…In the current study, the cell membrane depolarization was found in the C. sakazakii strains after treatment with CBCE. Similar results have been reported in previous studies on the bacteriostatic process on nopal cactus methanolic extracts against Vibrio cholerae , lipoic acid against C. sakazakii , and ATCE against Staphylococcus aureus ( Sánchez et al, 2010 ; Shi et al, 2016c ; Guo L. et al, 2020 ). As a comparison, the cell membrane hyperpolarization was observed in the C. sakazakii cells treated by citral and syringic acid ( Shi et al, 2016a,b ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In the current study, the cell membrane depolarization was found in the C. sakazakii strains after treatment with CBCE. Similar results have been reported in previous studies on the bacteriostatic process on nopal cactus methanolic extracts against Vibrio cholerae , lipoic acid against C. sakazakii , and ATCE against Staphylococcus aureus ( Sánchez et al, 2010 ; Shi et al, 2016c ; Guo L. et al, 2020 ). As a comparison, the cell membrane hyperpolarization was observed in the C. sakazakii cells treated by citral and syringic acid ( Shi et al, 2016a,b ).…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have taken the change in bacterial protein as one of the important ways to reveal the antibacterial mechanism of natural products and found that the bacterial protein of the tested bacteria significantly decreased after the treatments with natural products ( Pasqua et al, 2010 ; Wang et al, 2015 ; Fei et al, 2018a ; Guo L. et al, 2020 ). Chen et al (2017) reported that the reduction of bacterial protein was associated with the increase of membrane permeability and obstruction in protein expression and synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The antibacterial activity of E. hirta extracts was investigated using the disk diffusion method with some modifications [35][36][37]. The bacterial suspension phase in physiological saline reaches a concentration of McFarland (0.5%) (equivalent to 10 8 CFU/mL).…”
Section: In Vitro Antibacterial Activity Using Disc Diffusion Methodsmentioning
confidence: 99%